2014
DOI: 10.2135/cropsci2013.05.0314
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution of Protein and Oil Compositions of Soybean Cultivars in China

Abstract: Soybean [Glycine max (L.) Merr.] seed, which contains high levels of oil and protein, is one of China's most important native crops. The aim of this study was to investigate how regional and environmental factors affect the compositions of protein, amino acids, oil, and fatty acids. A total of 127 soybean cultivars from four main regions of China were analyzed. The levels of total protein and most of amino acids showed a trend of increasing from Northern to Southern China, while the levels of total oil, steari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
42
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 20 publications
13
42
3
Order By: Relevance
“…Similarly, in lupin seeds, a negative correlation was reported between CP and starch content (Straková et al 2006). The negative correlation between protein and fat found in our study is in line with previous reports in soybean (Sakla et al 1988;Tajuddin et al 2003;Haghi et al 2012;Qin et al 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, in lupin seeds, a negative correlation was reported between CP and starch content (Straková et al 2006). The negative correlation between protein and fat found in our study is in line with previous reports in soybean (Sakla et al 1988;Tajuddin et al 2003;Haghi et al 2012;Qin et al 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Average protein was lower (421 and 425 g kg −1 ) in the Guelph and Ridgetown programs, respectively, while oil was higher (200 and 204 g kg −1 ), compared with Guelph historical cultivars with 428 g kg −1 protein and 191 g kg −1 oil. The ranges of oil and protein values across the germplasm groups were similar to those reported in germplasm surveys, such as Qin et al (2014) with an oil range of 142 to 228 g kg −1 across 127 Chinese cultivars, and Song et al (2016) with an oil range of 142 to 240 g kg −1 across 763 Chinese cultivars. These two studies reported 318 to 498 g kg −1 and 312 to 498 g kg −1 protein, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Correlations for oil and protein in this study were similar in magnitude and direction as reported by Cober and Voldeng (2000), who estimated the correlation for single cross experimental genotypes at r = −0.84 and for experimental backcross genotypes at r = −0.86. In another study using 127 Chinese genotypes, a correlation of r = −0.716 was reported between oil and protein (Qin et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…is an important grain and oilseed crop (Qin et al, 2014). The demand for soy products in China is rapidly increasing, and the Chinese soybean import market has strongly grown in recent years (He et al, 2013).…”
Section: Introductionmentioning
confidence: 99%